2021
DOI: 10.2174/1570161118666201015152921
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Diagnosis, and Treatment with 3 Different Statins of Non-alcoholic Fatty Liver Disease/Non-alcoholic Steatohepatitis in Military Personnel. Do Genetics Play a Role?

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) and its severe form, non-alcoholic steatohepatitis (NASH), are major health problems worldwide. Genetics may play a role in the pathogenesis of NAFLD/NASH. Aim: To investigate the prevalence of NAFLD/NASH in 5,400 military personnel and evaluate the effect of treatment with 3 statins on NAFLD/NASH using 2 non-invasive scores [NAFLD Activity Score (NAS); Fibrosis-4 score (FIB-4)]. Methods: During the mandatory annual medical check-up, military personnel u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Interestingly, in a recent systematic review and metanalysis it was described that in the interventional studies, ALT, AST and gamma-glutamyltransferase (GGT) were reduced after statin treatment on average between 25 and 35%, while observational studies showed an effect null, suggesting the hepatic safety of statins in patients with NAFLD [153]. Moreover, genetics may play a role in the pathogenesis of NAFLD/NASH and its treatment with statins [154].…”
Section: Statinsmentioning
confidence: 99%
“…Interestingly, in a recent systematic review and metanalysis it was described that in the interventional studies, ALT, AST and gamma-glutamyltransferase (GGT) were reduced after statin treatment on average between 25 and 35%, while observational studies showed an effect null, suggesting the hepatic safety of statins in patients with NAFLD [153]. Moreover, genetics may play a role in the pathogenesis of NAFLD/NASH and its treatment with statins [154].…”
Section: Statinsmentioning
confidence: 99%
“…However, statin treatment was associated with significantly reduced NAS and FIB-4 scores at the end of follow up. This benefit was relevant for all statins used in this study[ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…54 Improvement in cardiac risk profiles using lipidmodifying agents such as statins and ezetimibe reduce the risk of cardiovascular disease in the context of NAFLD. [132][133][134] Simon et al…”
Section: Lipid-modifying Medicationsmentioning
confidence: 99%